Masalah Pembiayaan Pendidikan di Indonesia: Kenaikan Biaya Pendidikan - Arsal, Fathur Riyadhi; Hidayat, Ara (CV. PUSDIKRA MITRA JAYA, 2024)
The cost of education is becoming increasingly expensive. According to an article quoted by detikedu citing BPS statistics, the cost of education rises by 10% to 15% each year. It should be realized that unequal education as a result of the high cost of education will affect all elements of social life. Education is not only expensive in public and private schools or educational institutions. This research uses a literature research approach. The literature search used keywords such as